Experimental Study and Finite Element Analysis of Critical Stresses of Reinforced Thermoplastic Pipes under Various Loads - Li, G.H.; Wang, W.J.; Jing, Z.J.; Ma, X.C.; Zuo, L.B. (Проблемы прочности, 2016)
In this paper, reinforced thermoplastic pipes (RTP) were studied under various loads. A total of five groups of specimens were designed to study the mechanical properties of RTPs under internal pressure, bending, a combination of internal pressure and bending moment, external pressure, and tension. This study obtained the bursting pressure of RTPs under internal pressure, the minimum bending radius under the bending moment, and the failure pressure under external pressure. At the same time, the mechanical properties of RTPs under various loads were analyzed using the finite element analysis. Analytical results agree well with the experimental ones. The finite element model established in this paper can be used for further research on the mechanical properties of RTPs.